Alcohol dependence and driving: knowledge of DVLA regulations. (February 2015) - Collier, Andrew; Watts, Maggie; Ghosh, Sujoy; Rice, Peter; Dewhurst, Neil
Abstract : Aims and Methods: The UK's Driver Vehicle Licensing Authority (DVLA) requires individuals to report if they have a medical condition such as alcohol dependence. General Medical Council guidance indicates that medical practitioners should ensure patients are aware of their impairment and requirement to notify the DVLA. Results: In a survey of 246 people with known alcohol dependence, none were aware of advice on driving given by medical practitioners and none had self-reported. In addition, 362 doctors, either attending a college symposium or visiting a college website, were asked about their knowledge of DVLA regulations regarding alcohol dependence: 73% of those attending the symposium and 63% of those visiting the website answered incorrectly. In Scotland, over 20000 people have alcohol dependence (over 1 million people with alcohol abuse), yet only 2548 people with alcohol problems self-reported to the DVLA in 2011. Clinical implications: If the DVLA regulations were implemented, it could make an enormous difference to the behaviours of the driving public.